Facilitating start-ups in port-city innovation ecosystems: A case study of Montreal and Rotterdam. (July 2018) - Witte, Patrick; Slack, Brian; Keesman, Maarten; Jugie, Jeanne-Hélène; Wiegmans, Bart
Abstract: Facilitating start-ups located in the port-city interface is one of the current policy strategies of municipalities in many port-cities worldwide to encourage innovations in constantly evolving port areas. This could help the re-development of vacant ex-port land, while also offering new economic orientations for the city and the port. The aim of the paper is therefore to explore what conditions are needed to facilitate and encourage start-ups in innovation ecosystems in the port-city interface. The analysis is based on two in-depth case studies of the port-cities of Montreal (Canada) and Rotterdam (the Netherlands). The results indicate that government initiatives to actively facilitate start-ups in formerly industrialized port areas are quite successful. However, the functional linkages between start-ups and port activities remains rather limited, if not entirely absent, and the impact on the functioning of the innovation ecosystem at large is not substantial. Other factors such as capital, collaboration and proximity are valued more than the physical location of the start-up. In this, other actors in the ecosystem besides the municipality and the port authority also play a key role. Furthermore, start-ups often feel limited in their innovative capacity because of stringent regulations and institutional rigidness. Governments and port authorities could facilitate in this respect by working more demand-driven in terms of unburdening and creating more institutional support, instead of imposing top-down rules and regulations to try to govern the ecosystem, which in itself can be considered a contradiction in terms.